Action and object naming in schizophrenia - Kambanaros, Maria; Messinis, Lambros; Georgiou, Vassilis; Papathanassopoulos, Panagiotis (My University, 2010)
Patients with schizophrenia demonstrate impaired action verbal fluency, but no study has examined verb–noun differences using picture naming. The present study compared object and action naming in 20 adult patients diagnosed with schizophrenia (DSM–IV–TR, Diagnostic and Statistical Manual of Mental Disorders–Fourth Edition, Text Revision; American Psychiatric Association, 2000) criteria, and 20 demographically matched healthy controls, using pictures. Overall, schizophrenic patients showed poorer naming than controls on all measures of object and action lexical semantic access and retrieval despite normal comprehension for action and object names. Results further indicated that action names were significantly more difficult to retrieve than object names in schizophrenic patients. The absence of dissociation in comprehension of action and object names but semantic errors in naming both classes suggests intact conceptual–semantic stores among middle-aged community-dwelling outpatients with schizophrenia but difficulties mapping semantics onto the lexicon. Action-naming impairments can arise from both semantic and postsemantic origins in schizophrenia. These results have implications for the neurobiology of language given the association between both schizophrenia and verb processing and frontal damage. Moreover, the issue being addressed is important for a cognitive characterization of schizophrenia and for an understanding of the representations of action and object names in the brain.
Keywords: Schizophrenia spectrum disorder; Lexical access; Object and action picture naming; Instrumentality; Semantic errors